Clinical utility of anti-C1q antibody in primary and secondary vasculitic conditions - Jayakanthan, Kabeerdoss; Gupta, Nikhil; Mathew, John; Ravindran, Raheesh; Mahasampth, Gowri; Danda, Debashish (International Journal of Health Sciences, 2017)
Objective: Anti-C1q antibodies (Anti-C1q Ab) are seen in hypocomplementemic urticarial vasculitis syndrome (HUVS), infection-associated vasculitis such as hepatitis C virus-related vasculitis and in autoimmune diseases such as rheumatoid vasculitis, polyarteritis nodosa, giant cell arteritis, vascular Behcet’s disease, and cryoglobulin associated vasculitis. Aim of this study is to evaluate the presence of Anti-C1q Ab in vasculitis and to determine if any difference exists between primary and secondary vasculitis in relation to this antibody. Patients and Methods: Consecutive patients with diagnosis of either a primary or secondary vasculitis were recruited. Primary vasculitis were diagnosed by the American College of Rheumatology 1990 criteria. Clinical features and serological markers were noted. Anti-C1q Ab was assayed by commercially available ELISA kit (Demeditec Diagnostics GmbH, Germany). Results: Sixty-four patients were recruited for the study comprising of 41 primary vasculitis and 23 secondary vasculitis cases. No difference in Anti-C1q Ab levels between primary and secondary vasculitis was noted four patients were positive for Anti-C1q Ab out of the 64 patients. Of the four, one patient was diagnosed as HUVS, 2 patients as systemic lupus erythermatosus with vasculitis (16.7%) and another patient was diagnosed as rheumatoid arthritis with vasculitis (14.28%). Anti-C1q Ab negatively correlated with age and C3 but it correlated positively with erythrocyte sedimentation rate (ESR) in vascultic patients. Conclusion: Presence of anti-C1q Ab did not differ between the patients with primary and secondary vasculitis. Anti-C1q Ab titers correlated with younger age, high ESR, and low C3 in patients with vasculitis in our study.